Economic growth and the matters of inflation and unemployment: Evidence from ASEAN-5 - Tee, Elaine Ee-Lin; Gan, Pei-Tha; Hadi, Fatimah Salwa Abd; Zakaria, Zainizam (Asian Economic and Financial Review, 2024)
The purpose of this study is to examine the relationship between economic growth, inflation, and unemployment. One notable feature of empirical research is the rarity of studies that examine the effects of unemployment and inflation on economic growth in different economic environments, despite the large number of studies that look into these two variables. The study also incorporates interest rates and exchange rates as control variables. This study employs time series data spanning from 1994 to 2020 for selected 5 countries of the Association of Southeast Asian Nations (ASEAN), namely Indonesia, Malaysia, Singapore, Thailand, and the Philippines, under diverse economic conditions. The analysis utilises the autoregressive distributed lag (ARDL) method to examine the relationships between economic growth and its determinants. The empirical results of the study reveal: (1) Economic growth benefits from reducing inflation, interest rates, and exchange rates, underscoring their positive impact on development; and (2) Elevated unemployment rates hinder economic growth. These findings provide policy implications for policymakers in managing inflation, unemployment, interest rates, and exchange rates to foster sustained economic development.